Extended spectrum type CTX-M β-lactamases in clinical infections caused by Escherichia coli y Klebsiella pneumoniae at the Instituto Nacional de Salud del Niño-Breña, Lima, Peru - Gonzales, Edgar (2020)
Objective: To determine the frequency of extended spectrum β-lactamases (ESBL) in clinical infections caused by Escherichia coli y Klebsiella pneumoniae and the frequency of CTX-M among them at the Instituto Nacional de Salud del Niño-Breña, Lima, Peru. Methods: ESBL producing strains of E. coli and K. pneumoniae collected from August 2012 and January 2013 were analyzed; a total of 724 E. coli and 181 K. pneumoniae consecutive, non- repeated isolates from community and hospital acquired infections were included. Identification was performed by conventional biochemistry, ESBL phenotype was detected following the Jarlier´s method and PCR was used to detect CTX-M. Results: overall prevalence of ESBL was 31% (281 strains); 207/724 (28.6%) E. coli and 74/181 (40.9%) K. pneumoniae. The bla gene was detected in 256 of ESBL producing strains (91.1%). Conclusions: The CTX-M phenotype of ESBL producing strains is present in our institution. Despite of showing information of a single institution, these data bring a glance of what the antimicrobial resistance pattern may be at a national level and underscores the utility of molecular biology in designing preventing measures.